Comparison of a powered bone marrow biopsy device with a manual system: results of a prospective randomised controlled trial. Issue 1 (26th October 2012) - Bucher, Christoph Marcus; Lehmann, Thomas; Tichelli, André; Tzankov, Alexander; Dirnhofer, Stephan; Passweg, Jakob; Rovó, Alicia
Abstract : The diagnostic and clinical usefulness of a powered bone marrow biopsy device (OnControl()) versus a standard manual device (TRAP Hospital System) was studied. Primary endpoints were biopsy quality and patient pain during the procedure. Fifty patients underwent a total of 60 procedures by three expert operators in a randomised stratified fashion. Baseline demographic and clinical parameters were similar in both groups. The usage of conscious sedation, dosage of lidocaine/pethidin was similar between groups. Biopsy quality was rated 'sufficient for diagnosis' in 24/30 in the control group and 25/30 in the powered group (p=0.74). Biopsy cylinder length, procedure time (from skin contact of the biopsy needle to placement of the biopsy cylinder in the formalin container) and patient reported pain during the procedure (T1), 15 min after the procedure (T2) and 3–5 days after the procedure (T3) there were comparable between groups. In the small subgroup of patients that did not receive conscious sedation (n=15; manual 6, powered 9) significantly lower median pain scores were observed with the powered system (median pain score 3 vs 7; p=0.015). Patients were satisfied with either device whether sedation was used (sedation: median 9 for both groups, range 3–10 (manual) and 0–10 (powered)) no sedation (median 8 (manual) vs 9 (powered)). In summary bone marrow biopsies taken with the manual or powered device produce similar technical and clinical results. If no conscious sedation is used, pain during the procedure appears to be lower with the powered system. The use of a powered system seems to be justified in selected patients.